Interfacial thiol–isocyanate reactions for functional nanocarriers: a facile route towards tunable morphologies and hydrophilic payload encapsulation. Issue 87 (17th September 2015) - Kuypers, Sören; Pramanik, Sumit Kumar; D'Olieslaeger, Lien; Reekmans, Gunter; Peters, Martijn; D'Haen, Jan; Vanderzande, Dirk; Junkers, Thomas; Adriaensens, Peter; Ethirajan, Anitha
Abstract : Design of nanocarriers with tunable morphology using the in situ thiol–isocyanate interfacial reactions. Abstract : Functional nanocarriers were synthesized using an in situ inverse miniemulsion polymerization employing thiol–isocyanate reactions at the droplet interface to encapsulate hydrophilic payloads. The morphology of the nanocarriers is conveniently tunable by varying the reaction conditions and the dispersions are easily transferable to the aqueous phase.